PENERAPAN MODEL PEMBELAJARAN KOOPERATIF QUICK ON THE DRAW UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN REAKSI REDOKS DI KELAS X SMA NEGERI 1 KAMPAR KIRI - Lestari, Lili Lestari; Amran, Elva Yasmi Amran Yasmi; ', Rini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Research on the application of cooperative learning model Quick On The Draw has been conducted to improve student learning achievement on the topic stoichiometry at class X SMAN 1 Kampar Kiri. This research is experimental research with randomized control group pretest-posttest design. The sample took in the               20 January – 26 February 2013. The sample consisted of two classes, X2 class as experimental class and X3 class as control class. Experimental Class is the class with cooperative learning model Quick On The Draw and Control Class is the class with no cooperative learning model Quick On The Draw. Analyze of data by used t-test formula. Result of data processing obtained tcount>ttable is 2,622 > 1,67. It means that the application of cooperative learning model Quick On The Draw can improve student achievement on the topic redoks at class X SMAN 1 Kampar Kiri. The category of the increasing learning achievement in experiment group included into high level by the normalized score gain (N – gain) was 0.73. Keyword: cooperative learning, quick on the draw, learning achievement, redoks